Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV METEOR during cruise M176 - Jörg Geldmacher; Anne-Cathrin Wölfl (PANGAEA, 2024)
Raw multibeam bathymetry data were collected aboard R/V Meteor during cruise M176 using a Kongsberg EM122 multibeam echosounder. The expedition took place during 2021-07-31 - 2021-08-29 from Emden - Emden (Germany) in the Northern Atlantic Ocean. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. Due to technical issues of the echosounder that were encountered during the cruise, the data are erroneous. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Acquisition and provision of the data are part of the DAM Underway Project.